The Mars crustal magnetic field control of plasma boundary locations and atmospheric loss: MHD prediction and comparison with MAVEN. Issue 4 (10th April 2017) - Fang, Xiaohua; Ma, Yingjuan; Masunaga, Kei; Dong, Yaxue; Brain, David; Halekas, Jasper; Lillis, Robert; Jakosky, Bruce; Connerney, Jack; Grebowsky, Joseph; Dong, Chuanfei
Abstract: We present results from a global Mars time‐dependent MHD simulation under constant solar wind and solar radiation impact considering inherent magnetic field variations due to continuous planetary rotation. We calculate the 3‐D shapes and locations of the bow shock (BS) and the induced magnetospheric boundary (IMB) and then examine their dynamic changes with time. We develop a physics‐based, empirical algorithm to effectively summarize the multidimensional crustal field distribution. It is found that by organizing the model results using this new approach, the Mars crustal field shows a clear, significant influence on both the IMB and the BS. Specifically, quantitative relationships have been established between the field distribution and the mean boundary distances and the cross‐section areas in the terminator plane for both of the boundaries. The model‐predicted relationships are further verified by the observations from the NASA Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. Our analysis shows that the boundaries are collectively affected by the global crustal field distribution, which, however, cannot be simply parameterized by a local parameter like the widely used subsolar longitude. Our calculations show that the variability of the intrinsic crustal field distribution in Mars‐centered Solar Orbital itself may account for ∼60% of the variation in total atmospheric loss, when external drivers are static. It is found that the crustal field has not only a shielding effect for atmospheric loss but also an escape‐fostering effect by positively affecting the transterminator ion flow cross‐section area. Plain Language Summary: The inhomogeneous crustal magnetic field at Mars has important controlling effects on the Mars‐solar wind interaction and has both shielding and escape‐fostering effects on atmospheric erosion. Key Points: The Mars crustal field has a clear, significant influence on both the IMB and the BS The global crustal field distribution collectively affects IMB and BS locations The crustal field has both shielding and escape‐fostering effects for atmospheric loss